2012
DOI: 10.1093/cid/cir1039
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Early Outcomes of Patients With Xpert MTB/RIF-Negative Pulmonary Tuberculosis Diagnosed During Screening Before Antiretroviral Therapy

Abstract: Comparison of the characteristics of HIV-infected patients with Xpert-positive and Xpert-negative tuberculosis and relationship of Xpert status with subsequent clinical and programmatic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
49
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 20 publications
8
49
1
8
Order By: Relevance
“…A modest neutrophilic response was common in tuberculosis: even survivors with active tuberculosis had higher median neutrophil counts than healthy contacts. Others have reported that higher blood neutrophil counts correlate with sputum M. tuberculosis PCR positivity and, especially, smear positivity [7], while separate studies discovered higher neutrophil counts associated with slower conversion of sputum culture to negative [5,6]. Together with the higher prevalence of neutrophilia in patients who die (reported here), these results suggest that, broadly speaking, the neutrophil count in tuberculosis positively correlates with bacillary load.…”
Section: Neutrophilia Independently Predicts Death In Tuberculosissupporting
confidence: 65%
“…A modest neutrophilic response was common in tuberculosis: even survivors with active tuberculosis had higher median neutrophil counts than healthy contacts. Others have reported that higher blood neutrophil counts correlate with sputum M. tuberculosis PCR positivity and, especially, smear positivity [7], while separate studies discovered higher neutrophil counts associated with slower conversion of sputum culture to negative [5,6]. Together with the higher prevalence of neutrophilia in patients who die (reported here), these results suggest that, broadly speaking, the neutrophil count in tuberculosis positively correlates with bacillary load.…”
Section: Neutrophilia Independently Predicts Death In Tuberculosissupporting
confidence: 65%
“…9,[49][50][51] The performance of all tests tends to be less good due to lower sensitivity when used for screening than for patient-initiated diagnostic testing, as the spectrum of undiagnosed disease detected is shifted towards earlier, paucibacillary cases (Figures 2 and 3): this includes culture, smear microscopy and Xpert. 30,41,49,50,[52][53][54] There is considerable incremental yield from combining different tests, or repeating the same test on different specimens. 30,53,55 All tests also have relatively low positive predictive value when used for screening, due to the lower prevalence of true disease.…”
Section: Optimal Screening Strategies For Different Priority Groupsmentioning
confidence: 99%
“…The Xpert MTB/RIF assay is highly sensitivity and much faster than sputum microscopy 35 . Therefore, the rate of detection is increased by 45%, when compared with sputum microscopy, for the patients those are infected by HIV 36 . The Xpert MTB/RIF assay has the possibilities to improve the performance of national tuberculosis programs and currently being implemented in 67 countries 3 .…”
Section: Active Tuberculosismentioning
confidence: 99%